THE CRIME OF SAME-SEX ABUSE AGAINST MINORS (JURIDICAL ANALYSIS OF LUBUK SIKAPING STATE COURT RULING NUMBER 16/PID.SUS/2022/PN LBS) - Darlisma, Darlisma; Fauzia Zainin; Jasmalinda, Jasmalinda (Ikatan Dosen Menulis, 2025)
Many cases are found in public life, in the mass media, both in print and electronic media regarding crimes and sexual violence, especially against minors. Obscenity is a sexual crime or disgraceful act that often occurs in society. Obscene acts are all acts that violate decency or are heinous acts that are in the nature of lust or sexual lust. Same-sex sexual abuse is an act that violates decency or decency, or it can also be a vile act that falls within the scope of genital lust, which is committed against people of the same sex, namely between men and men or between women and women. The purpose of this research is to examine the application of criminal law against perpetrators of criminal acts of same-sex sexual abuse of minors in Decision Number 16/Pid.Sus/2022/PN Lbs and to examine the basic legal considerations for judges in imposing criminal sanctions against perpetrators of same-sex sexual abuse of children. underage (juridical analysis of Lubuk Suhuing District Court Decision Number 16/Pid.Sus/2022/PN Lbs). The research carried out is empirical legal research using a sociological juridical approach method by taking primary data, namely from data taken in the field, through interviews with interested parties or respondents and secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the research, it was found that in the application of criminal penalties to perpetrators of the crime of same-sex sexual abuse of minors in Decision Number 16/Pid.Sus/2022/PN Lbs at the Lubuk Suhuing District Court, the panel of judges sentenced them to prison for 11 (eleven) months. The basis for legal considerations for judges in imposing criminal sanctions on perpetrators of criminal acts of same-sex sexual abuse against minors, namely the statements of witnesses, the defendant's statement, letters, instructions and the judge paying attention to the legal facts in the trial. When providing legal considerations to impose criminal sanctions on perpetrators, the panel of judges should pay attention to the elements of justice and benefit, so that they can have a deterrent effect on the defendant or convict and on other people in the community so that it is not easy for them to commit criminal acts like this case. The community, especially parents, should increase their awareness of their children and it is hoped that the community will increase their faith and devotion to Allah SWT in order to avoid wrong actions and bad intentions. Key words: criminal acts, sexual abuse, same sex, minors